Evaluation of Intrahepatic Bile Duct Variations in Magnetic Resonance Cholangiopancreatography - Paudel, Sulav; Joshi, Birendra Raj; Chand, Ram Bahadur (Nepalese Journal of Radiology, 2020)
Introduction: A detailed knowledge of normal branching pattern of intrahepatic bile duct and their variations is of utmost importance for any liver or biliary tract surgery to avoid severe post-surgery complications and morbidity. The objective of this study was to evaluate variations of intrahepatic bile ducts in Magnetic Resonance Cholangiopancreatography (MRCP) examinations in Nepalese population. Methods: This quantitative, cross sectional study was performed in patients referred for MRCP examinations for various clinical indications to Tribhuvan University Teaching Hospital, Maharajgunj, Nepal. Data were collected for a period of four months from August to November 2019 after IRB approval. Convenience sampling was employed and a total of 90 examinations were included. Data were obtained from the 1.5T Magnetom Amira Siemens MRI scanner. The 3D MRCP images were visually analyzed and classified into 7 Types according to the classification given by Choi et al. Results: In our study 47.8% patients had Type 1/normal IHBD (n=43). 20% had Type 2 (n=18), 3.3% had Type 3A (n=3), 5.6% had Type 3B. Type 5A (n=5), 7.8% had 5B (n=7), 3.3% had Type 6 (n=3) and 6.7% had Type 7 (n=6). No patients were found to have Type 3C and Type 4 IHBD variation. Among the total number of Type 1 cases, 67.44% (n=29) were female and rest were male. Conclusions: Typical IHBD was only found in a 47.8% patients and common other variations were also noted in our population. Type 2 and Type 5B were found in 20% and 7.8% patients respectively.